(3GdYQi GdYGUeI aj JaVjd aGWeIs - (3GdZQGhj, eMeO QVG Hf bGSe Hf eMeO, J(B1385(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3GdMeO ddg Pj GdLhO hGdhdGA hGdeLO hGdcHQjGA(B... (3hgPG ChGf GdTQhY aj GdebUhO(B...s
(3BNQgG (B:s
(3Cbhd hjcajfG aj QSe GdCOdI GdcKjQI aj gPg GdChQGb GdjSjQI Ydi KHhJ CaVdjJgG Ydi GdCfHjGA GdSGdajf(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B6(3,U(B128s
(3GdPQjYI(B:(3L(B15(3,Qbe(B1687s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs